1996
DOI: 10.1136/gut.38.4.538
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II gene frequencies in Crohn's disease: a population based analysis in Germany.

Abstract: Background-Ulcerative colitis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 19 publications
5
25
0
2
Order By: Relevance
“…In other serologic studies, the HLA class II DR1-DQ5 haplotype was found to be associated with CD in Caucasians [12,15,25]. Moreover, recent molecular analyses of the HLA class II genes in Japanese [16,23,24] and Caucasian populations [13,[26][27][28] (including the current study) demonstrated significant HLA class II allele and haplotype associations with IBD.…”
Section: Introductionsupporting
confidence: 65%
“…In other serologic studies, the HLA class II DR1-DQ5 haplotype was found to be associated with CD in Caucasians [12,15,25]. Moreover, recent molecular analyses of the HLA class II genes in Japanese [16,23,24] and Caucasian populations [13,[26][27][28] (including the current study) demonstrated significant HLA class II allele and haplotype associations with IBD.…”
Section: Introductionsupporting
confidence: 65%
“…The up-regulation of antigen presentation genes is consistent with increased expression of HLA Class II molecules that typically occurs in IBD in humans [29]. HLA Class II genes have been associated with risk of IBD in a number of populations [30,31] (reviewed in ref. [32]).…”
Section: Discussionmentioning
confidence: 83%
“…Earlier CD onset was associated with more frequent CD flares, 59 a positive family history, 60 positive tests for antiSaccharomyces cervisiae antibodies, 61 presence of HLA DR7, 62 extensive jejunal and ileal involvement with CD, 63 upper gastrointestinal involvement, 64 and a need for at least one surgical procedure. 64 65 Presence of epithelioid granulomas in CD patients was strongly associated with a higher rate of postoperative recurrence (that is, with a need for two surgical procedures).…”
mentioning
confidence: 99%